2015
DOI: 10.1007/s00330-015-4132-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 18F-FDG PET/CT on Staging and Prognosis in Patients with Small Cell Lung Cancer

Abstract: • Identifying variables that predict the prognosis of patients with SCLC is important. • 18F-FDG PET/CT influences staging of patients with SCLC. • Metabolic parameters could be used as predictors for PFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 14 publications
1
35
0
2
Order By: Relevance
“…We used the univariate HR and 95% CI from each eligible article, except for the study by Zer et al . where only adjusted HRs from multivariate analyses were obtainable . Two studies by the same group (Oh et al .)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the univariate HR and 95% CI from each eligible article, except for the study by Zer et al . where only adjusted HRs from multivariate analyses were obtainable . Two studies by the same group (Oh et al .)…”
Section: Methodsmentioning
confidence: 99%
“…This included primary tumour, lymph nodes, and distant metastases. Three studies measured MTV and TLG only in the thorax (MTV TRX and TLG TRX ) . The remaining study evaluated both MTV WB and MTV TRX .…”
Section: Methodsmentioning
confidence: 99%
“…These studies showed that 18 F-FDG PET or 18 F-FDG PET/CT upstages 0% to 47% of limited-stage patients, but the results are inconsistent and many studies had significant bias. 16,18,19,29 Additional references are listed in Supplement 2. Furthermore and unlike in NSCLC studies, the rapid SCLC doubling time, coupled with the lack of need for precise anatomic histological staging to inform treatment decisions, has nearly always precluded histological validation of 18 F-FDG PET or 18 F-FDG PET/ CT findings.…”
Section: F-fdg Pet/ct Is Not As Well Established In Sclcmentioning
confidence: 99%
“…15 Small retrospective and nonrandomized prospective studies have shown that 18 F-FDG PET or 18 F-FDG PET/CT improves SCLC staging accuracy, with pretreatment metabolic and volumetric 18 F-FDG PET parameters providing additional prognostic information. [16][17][18][19] Oncology practice guidelines (e.g., the National Comprehensive Cancer Network guidelines) now recommend or suggest using 18 F-FDG PET/CT when staging patients with SCLC. [20][21][22][23] However, landmark phase 3 trials that established chemoradiotherapy as standard treatment in limited-staged SCLC were performed before the 18 F-FDG PET/CT era.…”
Section: Introductionmentioning
confidence: 99%
“…Yaygın hastalığın belirlenmesinde FDG PET/BT görüntülemenin tanısal rolünü araştıran çalışmaların incelendiği bir meta-analiz çalışmasında ortalama duyarlılık ve özgüllük değerleri sırarıyla %97 ve %98 olarak bulunmuştur (Tablo 2) (36). Evrelemede FDG PET/BT görüntülemenin kullanılması KHAK evresinde ve tedavi planında %11-%37 oranında değişikliğe neden olmaktadır (37,38,39). Akciğer kanserinde genel olarak gözlenen SUV maks ve metabolik tümör volümü (MTV) değerleri ile sağkalım arasındaki ilişkiler KHAK için de geçerlidir (39,40,41).…”
Section: Küçük Hücreli Akciğer Kanserinde Evrelemeunclassified